Spiritual Equilibrium: Syaikh Abdurrauf Singkel’s Concept of Tazkiyat al-Nafs - Nur Hadi Ihsan; Allan Muhammad; Muhammed Nur Kaplan; Arif Afandi Zarkasyi (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
The pursuit of worldly abundance and immersion in fleeting pleasures has quietly shaped the spirit of contemporary society, leading to a subtle yet profound imbalance within the human soul. By placing transitory possessions and temporal delights at the center of life's purpose, these tendencies have contributed to a deep spiritual estrangement. This study examines Syaikh Abdurrauf Singkel's concept of Tazkiyat al-nafs (soul purification) as a comprehensive spiritual framework for restoring harmony between the material and the spiritual. Drawing upon Singkel's Sufi teachings, this research explores how his methodology offers a pathway toward Insān kāmil (the perfect human)—a being who integrates worldly responsibilities with elevated spiritual consciousness. Employing a qualitative-descriptive approach through library research, the study analyzes Singkel's seminal works, including Tanbīh al-Mashyī, Mir'at al-Ṭullāb, Daqāiq al-Ḥurūf, and 'Umdat al-Muhtājīn. The findings reveal how classical Islamic spiritual disciplines—dhikr (remembrance of God), muhāsaba (self-reflection), murāqaba (divine vigilance), and tawakkal (trust in God)—serve as an enduring guide to addressing the restlessness born of excessive worldly attachment and the allure of transient joys, offering a balanced and timeless path toward inner peace in the modern age. Contribution: This study reintroduces Syaikh Abdurrauf Singkel’s concept of Tazkiyat al-nafs as a spiritual response to the prevailing pursuit of worldly abundance and immersion in fleeting pleasures, offering a practical Sufi framework rooted in Islamic tradition to guide individuals toward Insān kāmil in today’s consumer-oriented society.